Effect of Leadership, Motivation, Training on Performance Through Employee Satisfaction of the Regional Secretariat of Bintan Regency - Syarifah Alda Azlika; Chablullah Wibisono; Gita Indrawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the direct and indirect effect of leadership, motivation, training on performance through employee satisfaction of the regional secretariat of bintan regency. This type of research uses quantitative research methods with primary and secondary data sources. The population in this study was 109 Civil Servants (PNS) who worked at the Bintan Regency Regional Secretariat office. In this study, data collection was carried out using the census method in which the entire population was taken as a sample. By using the census method, this study aims to obtain accurate and representative data from the entire existing population. This step will make it easier for researchers to analyze and describe the characteristics and events that occur in the population. This research uses Smart-Pls as a data processing tool. The results of this study, Leadership has a positive and significant effect on Employee Performance. This proves that Leadership can affect the Performance of Employees of the Bintan Regency Regional Secretariat. Motivation has a positive and significant effect on Employee Performance. This proves that Motivation can affect the Performance of Employees of the Bintan Regency Regional Secretariat. Training has a positive and significant effect on Employee Performance. This proves that Training can affect the Performance of Employees of the Bintan Regency Regional Secretariat. Job Satisfaction has a positive and significant effect on Employee Performance. This proves that Job Satisfaction can affect the Performance of Employees of the Bintan Regency Regional Secretariat. Leadership has a positive and significant effect on Employee Job Satisfaction. This proves that Leadership can affect the Job Satisfaction of Employees of the Bintan Regency Regional Secretariat. Motivation has a positive and significant effect on Employee Job Satisfaction. This proves that Motivation can affect the Job Satisfaction of Employees of the Bintan Regency Regional Secretariat. Training has a positive and insignificant effect on Employee Job Satisfaction. Job Satisfaction mediates positively and significantly between Leadership and the Performance of Employees of the Bintan Regency Regional Secretariat. Job Satisfaction mediates positively and significantly between Motivation and the Performance of Employees of the Bintan Regency Regional Secretariat. Job Satisfaction mediates positively and insignificantly between Training and the Performance of Employees of the Bintan Regency Regional Secretariat.